2022
DOI: 10.1021/acsestwater.2c00054
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Concentration, Recovery, and Normalization of SARS-CoV-2 RNA from Two Wastewater Treatment Plants in Texas and Correlation with COVID-19 Cases in the Community

Abstract: The purpose of this study was to conduct a correlative assessment of SARS-CoV-2 RNA concentrations in wastewater with COVID-19 cases and a systematic evaluation of the effect of using different virus concentration methods and recovery and normalization approaches. We measured SARS-CoV-2 RNA concentrations at two different wastewater treatment plants (WWTPs) in the Bexar County of Texas from October 2020 to May 2021 (32 weeks) using reverse transcription droplet digital PCR (RT-ddPCR). We evaluated three differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
2
15
0
Order By: Relevance
“…45,46 Wastewater samples collected during the third wave of COVID-19 cases (July–August 2021) showed relatively higher SARS-CoV-2 RNA concentrations as compared to other periods in the study area. 35,38 Notably, the SARS-COV-2 RNA levels were relatively lower from April–June 2021 and September–November 2021, which corresponded well with the initiation of vaccination in the study area and the decline in daily incident COVID-19 cases after the third wave, respectively. 34…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…45,46 Wastewater samples collected during the third wave of COVID-19 cases (July–August 2021) showed relatively higher SARS-CoV-2 RNA concentrations as compared to other periods in the study area. 35,38 Notably, the SARS-COV-2 RNA levels were relatively lower from April–June 2021 and September–November 2021, which corresponded well with the initiation of vaccination in the study area and the decline in daily incident COVID-19 cases after the third wave, respectively. 34…”
Section: Resultsmentioning
confidence: 71%
“…The results of the current study are consistent with those of previous studies which indicated that the SARS-CoV-2 N1 assay is more sensitive than the N2 assay and both are highly correlated. 35,43,44 During the rst three months of our study period, the average concentrations of both N1 and N2 gene targets were below 5000 copies per L. However, the trend in viral loads started to increase on July 5th and reached its peak on August 2nd, 2021, where the SARS-CoV-2 N1 and N2 concentrations in inuent samples were 2.8 × 10 4 copies per L and 5.2 × 10 3 copies per L, respectively.…”
Section: Sars-cov-2 Rna Detection In Raw Wastewater and Comparison Wi...mentioning
confidence: 84%
See 1 more Smart Citation
“…Recently, a significant number of studies have been published that improve confidence in the ability of WBE to assess SARS-CoV-2 transmission in the community. The topics addressed by these studies range from assessment and normalization of SARS-CoV-2 RNA in wastewater to a better understanding of the relationship between RNA load and COVID-19 clinical cases and hospitalization. The unique feature of our study is the evaluation of the relationship between wastewater RNA load and COVID-19 in an underserved community and the importance of elevating visibility of these communities to public health authorities.…”
Section: Discussionmentioning
confidence: 99%
“…Most WBS studies for COVID-19 focused on analyzing and monitoring wastewater samples taken from wastewater treatment plants (WWTPs) or hospitals [ 1 , 2 , 3 , 4 ]. Several studies showed a correlation between SARS-CoV-2 levels in wastewater and positive COVID-19 cases reported from clinic testing or public records, suggesting that wastewater-based monitoring can provide information for large-scale dynamic of the pandemic [ 5 , 6 , 7 , 8 , 9 ]. Although it is important to investigate the COVID-19 prevalence and dynamic in communities and cities scales, with the negative economic impact of the COVID-19 around the world, the interests of business owners lay in the presence of the viruses and infected individuals in the local facility, which is crucial for updating the control procedures in a timely manner to respond to the decreasing or rising risks and ensuring the safety of the workers during the business recovery stage [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%